Validity of self-reported height and weight in 4808 EPIC-Oxford participants - Spencer, E; Appleby, P; Davey, G; Key, T (Cambridge University Press, 2002)
Objective: To assess the validity of self-reported height and weight by comparison with measured height and weight in a sample of middle-aged men and women, and to determine the extent of misclassification of body mass index (BMI) arising from differences between self-reported and measured values. Design: Analysis of self-reported and measured height and weight data from participants in the Oxford cohort of the European Prospective Investigation into Cancer and Nutrition (EPIC-Oxford). Subjects: Four thousand eigh hundred and eight British men and women aged 35-76 years. Results: Speaman rank correlations between self-reported and measured height, weight and BMI were high (r>0.9, P<0.0001). Height was overestimated by a mean of 1.23 (95% confidence interval (CI) 1.11-1.34) cm in men and 0.60 (0.51-0.70) cm in women; the extent of overestimation was greater in older men and women, shorter men and heavier women. Weight was underestimated by a mean of 1.85 (1.72-1.99) kg in men and 1.40 (1.31-1.49) kg in women; the extent of underestimation was greater in heavier men and women, but did not vary with age or height. Using standard categories of BMI, 22.4% of men and 18.0% of women were classified incorrectly based on self-reported height and weight. After correcting the self-reported values using predictive equations derived from a 10% sample of subjects, misclassification decreased to 15.2% in men and 13.8% in women. Conclusions: Self-reported height and weight data are valid for identifying relationships in epidemiological studies. In analyses where anthropometric factors are the primary variables of interest, measurements in a representative sample of the study population can be used to improve the accuracy of estimates of height, weight and BMI.